Tetrakis(2‐cyanoethoxy)borate – An Alternative to Tetracyanidoborate‐Based Ionic Liquids. Issue 24 (21st June 2013) - Harloff, Jörg; Karsch, Markus; Lund, Henrik; Schulz, Axel; Villinger, Alexander
Abstract: This study examines the synthesis and properties of salts of the new tetrahedral [B(O–C2 H4 –CN)4 ] – anion, which can be synthesized by the reaction of tetrahedral NaBH4 and HO–C2 H4 –CN followed by salt metathesis. The structures of M[B(O–C2 H4 –CN)4 ] [M = Na, 1‐ethyl‐3‐methylimidazolium (EMIm), 1‐butyl‐3‐methylimidazolium (BMIm), 1‐octyl‐3‐methylimidazolium (OMIm), Me4 N, Et4 N, and Bu4 N] as well as the thermal decomposition products are discussed. Abstract : Salts of the new tetrahedral [B(O–C2 H4 –CN)4 ] – anion are obtained by the reaction of tetrahedral NaBH4 and HO–C2 H4 –CN followed by salt metathesis.